2014
DOI: 10.1016/j.neuroimage.2013.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state functional connectivity and reading abilities in first and second languages

Abstract: An intriguing discovery in recent years is that resting-state functional connectivity (RSFC) is associated with cognitive performance. The current study investigated whether RSFC within the reading network was correlated with Chinese adults’ reading abilities in their native language (L1, Chinese) and second language (L2, English). Results showed that RSFC within the reading network was positively correlated to reading abilities in L1 and L2, and RSFC between reading areas and the default network was negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 96 publications
2
26
0
Order By: Relevance
“…Our finding that the connectivity between the right MOG and the left STG was associated with faster reaction time in the CE group is consistent with one previous study, which found that greater connectivity between the left superior temporal gyrus and the right inferior occipital gyrus in a resting-state was correlated with faster word reading speed, measured by the Sight Word Efficiency subtest in the Test of Word Reading Efficiency (TOWRE-SWE) (Torgeson, Wagner, & Rashotte, 1999) in a group of native Chinese speakers who learned English (Zhang et al, 2014). It appears that the connectivity between the visuo-orthographic representation region (i.e.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our finding that the connectivity between the right MOG and the left STG was associated with faster reaction time in the CE group is consistent with one previous study, which found that greater connectivity between the left superior temporal gyrus and the right inferior occipital gyrus in a resting-state was correlated with faster word reading speed, measured by the Sight Word Efficiency subtest in the Test of Word Reading Efficiency (TOWRE-SWE) (Torgeson, Wagner, & Rashotte, 1999) in a group of native Chinese speakers who learned English (Zhang et al, 2014). It appears that the connectivity between the visuo-orthographic representation region (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, the connection strength between the visual word form area and the angular gyrus is correlated with proficiency in Spanish (Boukrina, Hanson, & Hanson, 2014). Another study of late Chinese-English bilinguals found that the relationship between resting-state functional connectivity and reading ability does not differ in L1 and L2 (Zhang et al, 2014). This study found that, in both L1 and L2, highly efficient word reading is associated with greater connectivity between the left fusiform gyrus and bilateral motor areas (e.g.…”
Section: Introductionmentioning
confidence: 55%
“…Reading abilities have been associated previously with variability in resting-state connectivity (Koyama et al, 2011;Zhang et al, 2014). Zhang et al (2014) reported that higher connectivity between visual and phonological processing regions corresponded with faster singleword reading. Anatomically, the VWFA is connected preferentially to the left perisylvian STG and left IFG.…”
Section: Discussionmentioning
confidence: 89%
“…To assess reading skill improvement, we adapted a measure (words per minute) that has been used previously to relate brain measures to reading abilities Thiebaut de Schotten et al, 2014;Zhang et al, 2014). Dehaene et al (2010) showed that activations in the VWFA were correlated positively with words read per minute in word and sentence reading.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation